2008
DOI: 10.1590/s1415-54192008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de seis tipos de braquetes ortodônticos quanto à força de adesão

Abstract: INTRODUÇÃO: a realização de um diagnóstico acurado, assim como a correta seleção de materiais, especificamente dos braquetes, são requisitos importantes para o êxito da terapia ortodôntica. OBJETIVOS: investigar a influência de variados tipos de desenho da base de braquetes na força de adesão. METODOLOGIA: seis modelos foram avaliados mediante ensaio de cisalhamento - Discovery (Dentaurum) - metálico com retenções por laser e 13,12mm² de área da base; Monobloc (Morelli) - metálico em corpo único com protuberân… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
4
12
1
1
Order By: Relevance
“…Wang et al [15], performed a laboratory study and their mean strengths of adhesion ranged from 4.32 to 9.32 MPa in tests performed on human teeth and six different bracket bases evaluated. Fleishman et al [5], found a variation of the adhesion strength means between 3.81 MPa (Edgewise Standard -Morelli) and 10.12 MPa (Discovery -Dentaurum). Fernandez et al [11], found forces varying from 4.32 to 7.65 MPa, in mesh and rail-shaped base brackets, bonded with conventional or self-etching adhesive.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Wang et al [15], performed a laboratory study and their mean strengths of adhesion ranged from 4.32 to 9.32 MPa in tests performed on human teeth and six different bracket bases evaluated. Fleishman et al [5], found a variation of the adhesion strength means between 3.81 MPa (Edgewise Standard -Morelli) and 10.12 MPa (Discovery -Dentaurum). Fernandez et al [11], found forces varying from 4.32 to 7.65 MPa, in mesh and rail-shaped base brackets, bonded with conventional or self-etching adhesive.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, adhesive excesses were removed without displacement of the bracket. For more legitimate comparisons between products, orthodontic adhesion strength tests should have a universal standardization [5,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A interface da fratura mais favorável para uma descolagem é a braquete\adesivo, com a retenção do adesivo na superfície do esmalte, pois isto demonstra que a força coesiva do esmalte foi superior a força de adesão da base do braquete ao adesivo (23). Nos experimentos utilizamos um bloco de cimento, onde foi colado o braquete, segundo metodologia de alguns trabalhos como Brunharo et al (25), pois é a interface onde ocorre o maior número de descolagens uma vez que a adesão esmalte/adesivo é comprovadamente mais segura.…”
Section: Página | 642unclassified